Association of altered lipid profile with disease activity, duration, and glucocorticoid treatment in patients with idiopathic inflammatory myopathies. (11th May 2021) - Oreska, S; Storkanova, H; Spiritovic, M; Hermankova, B; Vrablik, M; Pavelka, K; Senolt, L; Mann, H; Vencovsky, J; Tomcik, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): AZV CR, Czech health research council MHCR, Ministry of Health Dzech republic Background: Systemic inflammation, limited mobility, and glucocorticoid treatment in Idiopathic inflammatory myopathies (IIM) can have a negative impact on intermediate metabolic pathways, especially on lipid metabolism. Purpose: The aim of this study was to assess the differences in the lipid profile of IIM patients and healthy controls (HC) and the association with disease-specific features. Methods: 133 patients with IIM (106 females; mean age 60.3; disease duration 2.2 years; dermatomyositis, DM 47 / polymyositis, PM 41 / immune-mediated necrotizing myopathy, IMNM 45) and 133 age-/sex-matched HC (106 females, mean age 60.2) were included. Data are presented as median (IQR). Results: Several differences in disease activity, the dose of glucocorticoids, prevalence of comorbidities, and serum lipid levels were observed among the three subtypes of IIM. Lipid profile parameters, especially levels of negative cardiovascular predictive markers such as TC, TG, LDL-C, Apo-B, and the atherogenic index were significantly higher compared to HC. The most significant changes were observed in IMNM compared to age-/sex-matched HC. Levels of TC, TG, LDL-C, apo-B, and non-HDL negatively correlated with disease duration but positively with laboratory markers of disease activity and the current prednisone equivalent dose. Higher levels of HDL-C were associated with decreased levels of CRP, which is in line with the negative correlation of apo-A levels with CRP, CK, and myoglobin. Conclusions: We have observed significant alterations in serum lipid parameters in our IIM patients compared to healthy age-/sex-matched individuals. Differences were also found among the three IIM subtypes. These alterations were associated with laboratory parameters of disease activity and the current dose of corticosteroids.